Antibiotic Resistance Pattern of Pathogens (Gram positive cocci) of Adult Patients Admitted at a Tertiary Level Hospital of Dhaka City in Bangladesh (Bangladesh Journal of Infectious Diseases, 2025)
Background: Resistance pattern of the organism varies from one country to another and within the country. Regular monitoring and surveillance are necessary for curbing the emergence of resistant organisms and effective infection control in the hospital settings of Bangladesh.Objective: The purpose of the present study was to assess the sensitivity pattern of bacterial gram-positive cocci isolated from the clinical specimens.Methodology: This was a descriptive type of cross-sectional study. Sampling technique was purposive sampling technique was applied and data were collected by pretested semi-structured questionnaires and face to face interview. A total of 384 urine & blood samples were collected in sterile containers from suspected infected cases. A specimen was considered positive if an organism was cultured at a concentration of ≥105 CFU/ml or when an organism was cultured at a concentration of 104 CFU/ml and >5 pus cells per high power field. Antimicrobial susceptibility testing of the isolated bacterial species was performed by the disc diffusion method following the National Committee for Clinical Laboratory Standards (NCCLS) guidelines.Results: Sample size was 384 adult patients of Dhaka Medical College Hospital. Enterococci were found highly resistant to cefixime 50.00%, cloxacillin 75.00%, and erythromycin 90.00%. Due to widespread resistance of the drugs used to treat infection, the choice of drugs in the treatment of infection is quite narrow. In our country, awareness for prevention of infection should be encouraged at the community level as it affects all adult age groups. Staphylococcus aureus was 83.33% resistant to amoxycillin, 100.0% to cefradine, 66.66% to cefuroxime, 100.0% to cephalexin, 50.0% to cefixime, 66.66% to cloxacillin and erythromycin, and 100.0% to methicillin.Conclusion: A high prevalence of resistance to most antibiotics was detected, along with major gaps in surveillance and information gaps in the methodological data of the studies.Bangladesh Journal of Infectious Diseases, June 2025;12(1):62-68